Food-Induced Adverse Reactions: A Review of Physiological Food Quality Control, Mucosal Defense Mechanisms, and Gastrointestinal Physiology - Dongdong Guo; Chang Liu; Hongkang Zhu; Yuliang Cheng; Xiang Huo; Yahui Guo; He Qian (Toxics)
Although food is essential for the survival of organisms, it can also trigger a variety of adverse reactions, ranging from nutrient intolerances to celiac disease and food allergies. Food not only contains essential nutrients but also includes numerous substances that may have positive or negative effects on the consuming organism. To protect against potentially harmful components, all animals have evolved defense mechanisms, which are similar to antimicrobial defenses but often come at the cost of the organism’s health. When these defensive responses are exaggerated or misdirected, they can lead to adverse food reactions, where the costs outweigh the benefits. Furthermore, due to the persistent toxicity of harmful food components, the failure of defense mechanisms can also result in pathological effects triggered by food. This article review presents a food quality control framework that aims to clarify how these reactions relate to normal physiological processes. Organisms utilize several systems to coexist with symbiotic microbes, regulate them, and concurrently avoid, expel, or neutralize harmful pathogens. Similarly, food quality control systems allow organisms to absorb necessary nutrients while defending against low-quality or harmful components in food. Although many microbes are lethal in the absence of antimicrobial defenses, diseases related to microbiome dysregulation, such as inflammatory bowel disease, have significantly increased. Antitoxin defenses also come with costs and may fail due to insufficiencies, exaggerations, or misdirected actions, ultimately leading to adverse food reactions. With the changes in human diet and lifestyle, the failure of defense mechanisms has contributed to the rising incidence of food intolerances. This review explores the mechanisms of antitoxin defenses and analyzes how their failure can lead to adverse food reactions, emphasizing the importance of a comprehensive understanding of food quality control mechanisms for developing more effective treatments for food-triggered diseases.